The Use of Mind Mapping in Teaching Writing of Recount Text: A Qualitative Study at SMK Diponegoro Karanganyar - Yulia Fatmah; Inayatul Ulya (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2026)
Writing is an essential component of learning English as a foreign language that allows learners to communicate ideas, experiences, and information effectively through written texts. Despite its importance, many students encounter difficulties when writing recount texts, particularly in generating ideas, organizing information, and presenting events in chronological order. Mind mapping has been widely applied as a visual pre-writing strategy to assist learners in planning and developing their ideas before composing a text. This study explored the use of mind mapping in teaching students to write recount texts and examined students' opinions of its strengths and weaknesses. A qualitative approach was employed involving 28 tenth-grade students of SMK Diponegoro Karanganyar in the 2025/2026 academic year. Data were gathered using classroom observation, questionnaires completed by all participants, and semi-structured interviews with 11 students chosen through purposive sampling. The data were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate that the use of mind mapping successfully supported students during the planning stage by helping them generate ideas, organize information, and arrange events systematically before writing. Students also perceived the strategy as engaging and beneficial because it increased their confidence and participation during classroom activities. Nevertheless, several challenges were identified, including the additional time needed to construct mind maps, difficulties in determining appropriate keywords, and students' reliance on teacher guidance during the initial stages of implementation. Overall, the study suggests that mind mapping is a valuable instructional strategy for facilitating their writing ability to produce recount texts.